The Cyberspace in Relation to the Cultural Memory; Innovation Management and Education Excellence Vision 2020: from Regional Development Sustainability to Global Economic Growth - Loyko O. T. Olga Timofeevna; Mashkina O. M. Olga Mikhaylovna; Tolkacheva V. A. Valentina Aleksandrovna; Zeremskaya Yu. A. Yuliya Aleksandrovna; Dryga S. V. Svetlana Valerievna (2016, 2016)
Title screen